Post-glacial diatom-inferred aquatic changes in Sicamous Creek Lake, British Columbia, Canada - Voit, Andrea; Hebda, Richard; Racca, Julien; Pienitz, Reinhard; Walker, Ian; Raeder, Uta; Heinrichs, Markus (Revue des sciences de l’eau / Journal of Water Science, 2014)
Diatom analyses of sediments from a high elevation lake situated in an Engelmann Spruce - Subalpine Fir (ESSF) forest of south-central British Columbia, Canada, reveal long-term climate and water chemistry change. During the transition from the late-glacial / Pleistocene to the xerothermic early Holocene, small, benthic Fragilaria diatoms species that grew under low light conditions in Sicamous Creek Lake gave way to planktonic Cyclotella species that require open-water conditions. Warm temperatures in the mesothermic Holocene are indicated by smaller Cyclotella species and large, benthic pennate diatoms. Diatom communities reflected Neoglacial cooling in the late Holocene, with abundant Nitzschia fonticola and Achnanthes minutissima. Small, benthic Fragilaria regained abundance, suggesting cooling and conditions similar to the late-glacial interval. Diatom community composition responded to the deposition of the Mt. Mazama and Mt. St. Helens tephras, though the Mazama eruption caused greater change in relative abundance of various taxa within the assemblage. Correspondence analysis shows distinct communities have occurred since the initiation of sedimentation, likely due to climate controlled landscape and vegetation changes; diatom-inferred pH values using various models and training sets show limited acidification change occurred through the lake’s history.